Factors associated with mortality in patients with drug-susceptible pulmonary tuberculosis - Nahid, Payam; Jarlsberg, Leah G; Rudoy, Irina; de Jong, Bouke C; Unger, Alon; Kawamura, L Masae; Osmond, Dennis H; Hopewell, Philip C; Daley, Charles L (BMC infectious diseases, 2011)
Background Tuberculosis is a leading cause of death worldwide, yet the determinants of death are not well understood. We sought to determine risk factors for mortality during treatment of drug-susceptible pulmonary tuberculosis under program settings. Methods Retrospective chart review of patients with drug-susceptible tuberculosis reported to the San Francisco Tuberculosis Control Program from 1990-2001. Results Of 565 patients meeting eligibility criteria, 37 (6.6%) died during the study period. Of 37 deaths, 12 (32.4%) had tuberculosis listed as a contributing factor. In multivariate analysis controlling for follow-up time, four characteristics were independently associated with mortality: HIV co-infection (HR = 2.57, p = 0.02), older age at tuberculosis diagnosis (HR = 1.52 per 10 years, p = 0.001); initial sputum smear positive for acid fast bacilli (HR = 3.07, p = 0.004); and experiencing an interruption in tuberculosis therapy (HR = 3.15, p = 0.002). The association between treatment interruption and risk of death was due to non-adherence during the intensive phase of treatment (HR = 3.20, p = 0.001). The median duration of treatment interruption did not differ significantly in either intensive or continuation phases between those who died and survived (23 versus 18 days, and 37 versus 29 days, respectively). No deaths were directly attributed to adverse drug reactions. Conclusions In addition to advanced age, HIV and characteristics of advanced tuberculosis, experiencing an interruption in anti-tuberculosis therapy, primarily due to non-adherence, was also independently associated with increased risk of death. Improving adherence early during treatment for tuberculosis may both improve tuberculosis outcomes as well as decrease mortality.